Feasibility assessment on the independent selection of dialysis methods in ESRD patient after 3-month blood purification:A blood purification center observation study in the Xinjiang Uyghur Autonomous Region - ZHUANG Jing; Reziwanguli Abudula; JIANG-Hong (Linchuang shenzangbing zazhi)
Objective To investigate mastering of the patients with SRD(ESRD)with dialysis treatment of over 3 months about knowledge and advantages or shortcomings of the two dialysis therapies in our dialysis center, and evaluate the intention and feasibility of their independent selection of dialysis methods.Methods With convenient sampling,146 patients with ESRD,who started to conduct regular peritoneal dialysis in People’s Hospital of Xinjiang Uyghur Autonomous Region between January 2016 to December 2017,were selected and divided into the hemodialysis group(HD group,85 patients)and the peritoneal dialysis group(PD group,61 patients)according to their dialysis methods.A retrospect survey questionnaire was made to learn about demographic data,influencing factors of selection of the two dialysis modes and urine decrease during dialysis,and to analyze the intention and feasibility of the patients’ new selection of long-term dialysis.Results The HD patients most selected this dialysis mode(92.94%)mainly according to their physician’s introduction before dialysis,while the PD patients who independently selected PD had a big proportion(55.74%).There was statistically significant difference between the two groups(P<0.05).After three months of dialysis,over 70% of the patients learned about the knowledge and features of the two dialysis modes,but 90.59% patients in the HD group did not yet master the PD knowledge,with statistically significant difference between the two groups(P<0.05).The emergent dialysis records in the HD group were more than those in the PD group(P<0.05).24-hour urine volume before dialysis had no difference between the two groups,after 3 months of treatment the proportion of patients with decrease urine volume in the HD group was higher than that in the PD group(P<0.05).With 3 months of treatment and education,there were 41.18 and 19.67% patients in the HD and PD groups,respectively,who were willing to adjust their dialysis method.Conclusions Lack of sufficient knowledge about dialysis is the main factor affecting ESRD patient`s independent selection of dialysis methods.besides that,more experience of emergent dialysis also plays a vital role in their selection.Both 3-month experience of dialysis and the changes of urine volume in the course of different dialysis therapies contribute to accumulation of the knowledge and the practice of two dialysis methods.This makes it possible for ESRD patients to have the ability to select dialysis mode independently,and make them select suitable dialysis method based on their own specific conditions.